Initial clinical experience of ranibizumab therapy for neovascular age-related macular degeneration - Tryfon Rotsos (Dove Medical Press, 2010)
Tryfon Rotsos, Praveen J Patel, Fred K Chen, Adnan TufailMedical Retina Service, Moorfields Eye Hospital, London, UKPurpose: To describe the visual acuity and safety outcomes for the first 50 patients with neovascular age-related macular degeneration (nAMD) treated with ranibizumab at Moorfields Eye Hospital.Methods: A retrospective analysis of case notes from the first 50 consecutive patients with Primary Care Trust funding for ranibizumab therapy for nAMD. Visual acuity outcomes and adverse events were noted, as were service delivery-related indicators.Results: The mean (±standard deviation) age of the 50 patients was 81 ± 17 years. The mean follow-up of patients was 13.6 ± 2 (range 7.7–18) months. The mean change in visual acuity ± standard error was +4.6 ± 2.2 letters at the end of follow-up, with 26% gaining 15 letters or more. The mean (median) number of injections was 4.7 (4.5) per 12-month period. The mean (median) delay in Primary Care Trust funding approval was 35 days (32 days) prior to the final appraisal document from the National Institute of Health and Clinical Excellence.Conclusions: The real-world outcomes of ranibizumab therapy in this initial cohort of patients with nAMD are comparable with those reported in the pivotal, randomized, controlled trials using fewer injections and a prn strategy of retreatment to achieve the gain in visual acuity.Keywords: macular degeneration, retina, ranibizumab